2023
DOI: 10.1101/2023.02.27.23286512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Computational Fluid Dynamics Simulations of Coiled Aneurysms Using Finite Element Modeling

Abstract: Cerebral aneurysms are a serious clinical challenge, with ∼half resulting in death or disability. Treatment via endovascular coiling significantly reduces the chances of rupture, but the technique has failure rates between 25-40%. This presents a pressing need to develop a method for determining optimal coil deployment strategies. Quantification of aneurysm hemodynamics through computational fluid dynamics (CFD) has the potential to significantly improve the understanding of the mechanics of aneurysm coiling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…To address this limitation, Damiano et al 16 introduced a novel coil deployment technique utilizing the finite element method (FEM) that replicated the non‐uniform distribution of coils within the aneurysm and enabled the prediction of post‐treatment hemodynamics, which was supported by clinical studies. Patrick et al 17 demonstrated that using FEM technology can enhance the accuracy of CFD simulations of coils within intravascular aneurysms. Therefore, the combination of FEM and CFD holds significant potential for research on cerebral aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…To address this limitation, Damiano et al 16 introduced a novel coil deployment technique utilizing the finite element method (FEM) that replicated the non‐uniform distribution of coils within the aneurysm and enabled the prediction of post‐treatment hemodynamics, which was supported by clinical studies. Patrick et al 17 demonstrated that using FEM technology can enhance the accuracy of CFD simulations of coils within intravascular aneurysms. Therefore, the combination of FEM and CFD holds significant potential for research on cerebral aneurysms.…”
Section: Introductionmentioning
confidence: 99%